Characteristics of ZnO/CuO heterojunctions formed by direct bonding and PLD with bias voltage application. Issue 10 (6th August 2013) - Komatsu, Kazuya; Seno, Yuki; Komiyama, Takao; Chonan, Yasunori; Yamaguchi, Hiroyuki; Aoyama, Takashi; Chauveau, Jean‐Michel; Sallet, Vincent; Morhain, Christian; Feuillet, Guy
Abstract Current‐voltage (I–V) characteristics of the n‐ZnO/p‐CuO heterojunctions have been investigated by changing the composition of the ZnO films and by using the direct bonding technique to form the heterojunctions. A ZnO film was deposited on an n‐type ZnO ceramic substrate by the PLD technique with bias voltage application. The change of the PLD bias voltage caused the deviation from the stoichiometric condition for ZnO films and led to growth of different grain sizes. The n‐ZnO/ZnO specimens were directly bonded on p‐type CuO substrates at room temperature. Post annealing at 400 °C for 1 h improved the diode characteristic but more than about 3 h annealing deteriorated the I‐V characteristics. A deposition condition close to stoichiometric oxygen/zinc = 1 caused the largest activation energies for both the forward and the reverse currents while a slightly zinc‐rich condition caused a larger forward and a smaller reverse currents. This suggested the applicability of the direct bonding technique for fabricating excellent ZnO heterojunctions. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)